Muscarinic receptor-mediated phosphoinositide hydrolysis in rat brain - (:unkn) unknown (My University, 1999)
0

Objective: Activation of cholinergic muscarinic receptors leads to activation of membrane - bound phospholipase C, leading to generation of IP3 and diacylglycerol, The present study aimed at measuring muscarinic receptor-mediated phosphoinositide breakdown in three different regions of rat brain. Methods: Cortical, hippocampal and striatal slices labeled with [3H] myo-inositol were incubated with muscarinic agonist carbachol (Cch) and LiCI. Reaction was terminated by the addition of chloroform/methanol and labeled inositol phosphates were extracted from tissue. Individual [3H]- inositol phosphates were separated using anion exchange chromatography. Results: Cch caused a rise in IP1 formation, where the increase over basal in the cortex, hippocampus and striatum were 98%, 73% and 45%, respectively. Conclusion: Phosphoinositide turnover was stimulated by carbachol in all brain structures studied, with the most pronounced effects observed in the cortex and hippocampus.
Keywords: Genel ve Dahili Tıp